ANÁLISIS DE LA CALIDAD DEL SERVICIO QUE PRESTA, EL HOTEL REINA DEL CISNE DEL CANTÓN CATAMAYO, PROVINCIA DE LOJA - Guazha Romero, María José (2020)
The research presented as a general objective: “Analyze the quality of the service provided by the Hotel Reina del Cisne of the Catamayo canton, province of Loja”. To achieve compliance with the investigation, three specific objectives were proposed: Diagnose the current situation of the Reina del Cisne Hotel; An analysis of the environment was carried out with the purpose of knowing the current situation, through the diagnostic matrix based on the general data, legal regulations and requirements for two-star hotels, interviews were conducted aimed at the main stakeholders of the Hotel, obtaining As a result, the Hotel has all the requirements granted by the entities and requirements issued by the Ministry of Tourism, except with the Ministry of Environment and National Council of Disabilities, likewise it does not have a communication system and security cameras in the common areas of the Hotel; To evaluate the quality of service offered by the Hotel Reina del Cisne, it was carried out through the servqual method which is based on five dimensions which are: tangible aspects, reliability, responsiveness, security and empathy, then a questionnaire was developed of 22 statements to measure customer expectations and perception on a 5-point Likert scale. The results obtained indicated difficulties in the dimensions of tangible aspects, empathy, responsiveness and security, while in the dimension of reliability it was acceptable to customers; Finally, to propose strategies for improving the quality of service of the Hotel Reina del Cisne, proposals were designed for the Hotel, created based on the results obtained from the survey and the dimensions of the servqual model, for the tangibility a plan of development was developed. Hotel furniture and equipment improvement; implementation of an internal communication system in the rooms and design of employee uniforms and Hotel logo; Likewise, for empathy, a training plan for employees in customer service and hospitality was developed; a maintenance plan for additional services (swimming pool, sauna, Turkish, hydromassage, gym and aerobics room); in the same way for reliability a suggestion box and a process manual of the departments of the Hotel were implemented; while for training the staff was trained; and finally for security cameras were implemented inside and outside the Hotel. It is concluded that in a general analysis of the quality of service of the Hotel Reina del Cisne and through the servqual model, that the quality does not meet the expectations of the client by having a significant gap of -0.30 for which improvements to the Hotel service; As a recommendation, customer satisfaction must be continually measured in order to know their criteria and thoughts in order to improve the service, thus achieving loyalty to the best clients of the Hotel.